Efficacy and safety of tripterygium glycosides for active moderate to severe Graves' ophthalmopathy: a randomised, observer-masked, single-centre trial. Issue 2 (February 2021) - Ye, Xiaozhen; Zhao, Heng; Liu, Jun; Lu, Bin; Shao, Jiaqing; Wang, Jian
Abstract : Background: Tripterygium glycosides (TG) has been used to treat a spectrum of inflammatory and autoimmune diseases. Our preliminary studies have shown that TG is effective in the treatment of active Graves' ophthalmopathy (GO). Objective: We aimed to compare the efficacy and tolerability of TG with intravenous methylprednisolone (iv.MP) in patients with active moderate-to-severe GO. Methods: This study was an observer-masked, single-centre, block-randomised trial. Patients with active moderate-to-severe GO were randomly assigned to receive iv.MP (500 mg once per week for 6 weeks followed by 250 mg per week for 6 weeks) or with TG (20 mg tablet three times per day for 24 weeks). The primary endpoints were the overall response rate and the patients' quality of life at 12 and 24 weeks. Results: In this study, 161 patients were enrolled and randomised from 2015 to 2019. A total of 79 were randomly assigned to receive iv.MP and 82 to receive TG. A greater overall response rate was found in the TG group compared with the iv.MP group at week 24 (90.2% vs 68.4%, P = 0.000). Similarly, the patients' quality of life of the TG group showed a significantly higher response than the iv.MP group at week 24 (89.02% vs 72.15%, P = 0.001). The TG therapy showed a better CAS response than the iv.MP (91.5% vs 70.9% improved, P < 0.05), and up to 91.2% of patients were inactive. Also, the TG group showed a significantly higher improved rate of diplopia, proptosis, visual acuity, soft tissue involved and the decrease of eye muscle motility than the iv.MP group at week 24. Significantly more patients in the iv.MP group than the TG group experienced adverse events. Conclusion: Compared with iv.MP treatment, TG therapy is more effective and safer for patients with active moderate to severe GO.